Integration of Islam and Psychology: The Role of Self-Acceptance and Religiosity in Increasing Student Flourishing - Khurun Aini, Dewi; Darmuin; Siti Hikmah; Muhammad Afin Mursida; Muhammad Dzuhri Muzayyin (Program Studi Psikologi Islam, Fakultas Psikologi, Universitas Islam Negeri Raden Fatah Palembang, 2024)
Individual well-being is often assessed through flourishing, the highest level of subjective well-being, enabling individuals to pursue meaningful goals while fostering resilience. This study explores the role of self-acceptance and religiosity in promoting flourishing among students in Semarang. Using a quantitative associative causality method, the research involved 770 students sampled via convenience sampling, with data collected through the flourishing, self-acceptance, and religiosity scales. Multiple linear regression analysis revealed a significant relationship between self-acceptance, religiosity, and flourishing, explaining 62.6% of the variance. Students with high self-acceptance and religiosity demonstrate improved self-understanding and internalization of religious values, leading to enhanced positive emotions and life satisfaction. The integration of Islamic principles with psychological concepts contributes to inner peace and optimal functioning in daily life. Implications include the need for future research to examine additional factors, such as social support, in promoting flourishing. This study also contributes to theory by highlighting the value of combining religiosity and psychology to explain well-being. For societal impact, universities can implement programs fostering self-acceptance and religiosity to support students' mental health and personal growth. This approach can help students manage academic pressures and life challenges, promoting resilience and overall well-being. In conclusion, self-acceptance and religiosity are crucial for flourishing in students, enhancing their psychological well-being and resilience against mental health issues.